SANGAM OF RELIGIONS IN THE UNKNOWN CHRIST - Menacherry, Cheriyan (Asian Horizons, 2011)
The present article deals mainly with one of the main insights of Raymond Panikkar. A tribute to a great scholar Raymond Panikkar who passed away on 26th August 2010 at the age of 91, at his home in Tavertet, is befitting, I thought, perhaps by attempting to understand the deep insight in one of his main contributions: meeting of religions in the ‘Unknown Christ’. As if his farewell message in a statement from his residence in Tavertet dated January 26, 2010, Panikkar has expressed as one of his desires that other people may continue “to spread my message and the sharing of my ideals, even without me.”